Effect of Seed Pelleting on Seed Quality and Field Performance of Onion (Allium cepa) - REKHA PATIL; RAVI HUNJE (Seed Research, 2026)
An attempt was made to study the effect of seed pelleting on seed quality and field performance of two seed lots of onion seeds. Between the two seed lots, Fresh seed lot (L1) recorded significantly higher seed quality parameters and yield characters as compared to old seed lot (L2). Among the pelleting, pelleting with ZnSO4 (10 g/kg) recorded significantly highest growth and yield characters viz., field emergence, equatorial diameter, polar diameter, bulb yield per plant and bulb yield per hectare compared to other treatments. Therefore, pelleting with ZnSO4 helps in increase the field performance of onion var. Bhima Super.